A CONCEPTUAL FRAMEWORK FOR QUALITATIVE RESEARCH: A LITERATURE STUDIES - Guntur, Guntur (Seni Media Rekam ISI Surakarta, 2019)
The conceptual framework is an important part of a research. However, there is still a lot of research, especially among students who ignore it. Indeed the conceptual framework has a strategic position and role in research. This article discusses about the conceptual framework in qualitative research. Specifically, it is aimed at providing understanding and practical guidance for students who will and / or are preparing research plans for their final assignments. This article consists of four main section / part. The first section discusses the understanding of research and research frameworks. The second section discusses the conceptual framework in qualitative research. The third section discusses how to develop / arrange a conceptual framework for qualitative research. The final chapter is a conclusion.